Second Movement of Compartment 2, Car 7 for Vibraphone, Violin, Viola and Cello by Paweł Szymański in Light of Cognitive Musical Grammar - Kostka, Violetta (Interdisciplinary Studies in Musicology, 2019)
The article is composed of two parts. In the first I discuss Lawrence Zbikowski’s Foundations of Musical Grammar, published by Oxford University Press in 2017, which is one of the major musicological works inspired by the latest achievements in cognitive science. Musical grammar, sometimes called cognitive musical grammar by the author, is based mainly on two concepts: an analogy (the mapping of systematic structural relationships between a source domain and a target domain), and a dynamic process (a coherent sequence of phenomena that is distributed over time and typified by parametric modulation or change). The second part of the article is my attempt to apply Zbikowski’s theory to a piece of music. As a musical example I have chosen the second movement of Compartment 2, Car 7 for vibraphone, violin, viola and cello by Paweł Szymański. At the end I conclude that the composer created an analogy between music and a dynamic process known to us from everyday life ─ a journey by train, seen from a passenger’s perspective.